Dynamic Changes and Clinical Significance of Plasma Galectin-3 in Patients with Acute Ischemic Stroke Undergoing Endovascular Therapy - Yao M; Liang D; Zeng X; Xie X; Gao J; Huang L (Dove Medical Press, 2024)
Mingzheng Yao,1 Dan Liang,2 Xiuli Zeng,1 Xiaomei Xie,1 Jiali Gao,1 Li'an Huang1 1Department of Neurology, The First Affiliated Hospital, Jinan University, Guangzhou, People's Republic of China; 2Department of Neurology, The Sixth Affiliated Hospital, School of Medicine, South China University of Technology, Foshan, People's Republic of ChinaCorrespondence: Li'an Huang, Department of Neurology, The First Affiliated Hospital, Jinan University, Guangzhou, People's Republic of China, Email huanglian1306@126.comPurpose: Galectin-3 is a key regulator of microglial proliferation and activation and may have dual and time-dependent effects on ischemic stroke. This study aimed to prospectively investigate the dynamic changes in Galectin-3 levels in patients with acute ischemic stroke receiving endovascular therapy and its clinical significance.Patients and Methods: A total of 105 patients with acute ischemic stroke who underwent endovascular therapy were prospectively enrolled. Plasma Galectin-3 was quantitatively detected by an enzyme-linked immunosorbent assay before the operation and at 1 day, 3 days and 7 days after the operation. A linear mixed-effect model, Pearson correlation analysis and receiver operating characteristic (ROC) curve analysis were used to evaluate the dynamic changes in the plasma Galectin-3 concentration and its relationship with clinical outcomes.Results: Increases in plasma Galectin-3 levels at 1 day and 3 days after surgery were associated with early neurological deterioration and death (both P < 0.05). Increased Galectin-3 levels before surgery and at 1 day and 3 days after surgery were associated with poor prognosis (P < 0.05). Pearson correlation analysis revealed that Galectin-3 levels before surgery (r =0.318, P =0.002), at 1 day (r =0.318, P =0.001), 3 days (r =0.429, P < 0.001) and 7 days after surgery (r =0.340, P =0.001) were positively correlated with NIHSS scores. The ROC curve results showed that Galectin-3 concentration had a certain predictive value for death at 1 day (AUC=0.707, P=0.013), 3 days (AUC=0.708, P=0.016) and 7 days after the operation (AUC=0.708, P=0.016), but this predictive value was lower than that of the NIHSS score.Conclusion: In acute ischemic stroke patients receiving endovascular therapy, an increase in the plasma Galectin-3 levels were associated with death, poor prognosis, and early neurological deterioration. Galectin-3 levels were significantly correlated with the NIHSS score and had a certain predictive value for death.Plain Language Summary: Galectin-3 is a key regulator of microglial proliferation and activation and may have dual and time-dependent effects on ischemic stroke. However, relevant clinical studies are less at present. In this study, we found that an increase in the plasma Galectin-3 levels had significant values in death, poor prognosis, and early neurological deterioration in acute ischemic stroke patients receiving endovascular therapy at various times.Keywords: ischemic stroke, Galectin-3, endovascular therapy, inflammation, dynamic change, outcome